THE ARMENIAN-AZERBAIJANI CONFLICT IN NAGORNO KARABAKH (HUMAN RIGHTS VIOLATIONS IN THE PERSPECTIVE OF REGIONAL SECURITY) - Raja Fanny Fatahillah; Henny Saptatia Drajati Nugrahani (International Conference on Social and Islamic Studies, 2021)
This study focuses on the Azerbaijan-Armenian conflict in a disputed area in the Caucasus region, Nagorno Karabakh. This conflict gives rise to human rights violations. The war in Nagorno Karabakh was a geographical conflict as well as a socio-political one, which had occurred since 1870-World War I. It repeated in 1988-1994. In 2009-2016 the conflict struck again and was followed by weapons in 2016-2020. The third period of war has occurred since 2020 until now. The Armenian-Azerbaijani conflict occurs continuously, genocide, or ethnic conflict, which is a violation of human rights in the Caucasus region. The war in Nagorno Karabakh has resulted in the death of 1,000 civilians, the displacement of 40,000 ethnic Azerbaijanis from Nagorno Karabakh, and an exodus of 90,000 ethnic Armenians. The research questions in this study are, first, why did the Armenian-Azerbaijan conflict in Nagorno Karabakh last for a long period and cause human rights violations. Secondly, how the efforts for a peaceful solution in Nagorno Karabakh can be achieved through a regional security perspective. The research method used is a critical qualitative research method. Critical analysis is used to expose and offer alternative perspectives. This method uses an interdisciplinary and multidisciplinary approach to look more critically at the social reality that is happening. This research was conducted by operationalizing the regional security complex theory (RSCT) by Barry Buzan.